2021
DOI: 10.52011/133
|View full text |Cite
|
Sign up to set email alerts
|

Etiquetado nutricional de alimentos procesados (semáforo nutricional) y su relación con factores socioeconómicos, culturales, demográficos y publicitarios, según padres de niños entre 5-11 años de dos colegios de Quito

Abstract: Introducción: El etiquetado nutricional es una herramienta gráfica para notificar al consumidor sobre las propiedades nutricionales de un alimento lo que facilita su selección. El objetivo del presente estudio fue determinar la influencia del etiquetado nutricional y los factores socioeconómicos, culturales, demográficos, publicitarios en la selección de alimentos en un grupo de padres de niños entre 5-11 años en dos unidades educativas públicas y privadas de Quito. Métodos: Con diseño mixto, cuantitativo- tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
2
0
2
Order By: Relevance
“…Similar results were observed in a study carried out in the seventh district of Quito, and it was concluded that women use labeling more frequently than men do [ 25 ]. Another qualitative study concluded that the responsibility for the selection and preparation of food generally falls on mothers, with little participation from the fathers, thereby highlighting the female role in the selection of food at home [ 24 ]. These findings are important since women could assume a fundamental role in raising awareness about the use of the NTL in food purchasing decisions in different contexts, such as family and work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were observed in a study carried out in the seventh district of Quito, and it was concluded that women use labeling more frequently than men do [ 25 ]. Another qualitative study concluded that the responsibility for the selection and preparation of food generally falls on mothers, with little participation from the fathers, thereby highlighting the female role in the selection of food at home [ 24 ]. These findings are important since women could assume a fundamental role in raising awareness about the use of the NTL in food purchasing decisions in different contexts, such as family and work.…”
Section: Discussionmentioning
confidence: 99%
“…The following study covariates were used, which were selected based on previous studies on food labeling and the questions available in the ENSANUT 2018. The following variables were included: age group (18 to 49, 50 to 64, 65 and over) [ 24 ], sex (male, female) [ 25 ], educational level (none or literacy center, basic education, middle/high school, higher education) [ 24 ], marital status (without a partner, with a partner) [ 26 , 27 ], area of residence (urban, rural), geographic region (highlands, coast, Amazon, insular), poverty due to unsatisfied basic needs (not poor, poor) [ 28 , 29 ], ethnicity (non-indigenous, indigenous) [ 30 ], and understanding of the nutritional traffic light (no, yes) [ 24 ]. Regarding the poverty due to unsatisfied basic needs, in our study a household was classified as poor if it had any of the following household characteristics: high economic dependency, inadequate physical characteristics, overcrowding, without access to basic services, and those with children who do not attend school [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Resultados similares se observaron en un estudio realizado en el séptimo distrito de Quito, y se concluyó que las mujeres utilizan el etiquetado con más frecuencia que los hombres [25]. Otro estudio cualitativo concluyó que la responsabilidad de la selección y preparación de los alimentos recae generalmente en las madres, con poca participación de los padres, resaltando así el rol femenino en la selección de alimentos en el hogar [24]. Estas conclusiones son importantes, ya que las mujeres podrían asumir un papel fundamental en la concienciación sobre el uso del SN en las decisiones de compra de alimentos en diferentes contextos, como el familiar y el laboral.…”
Section: Discussionunclassified
“…Se utilizaron las siguientes covariables de estudio, las cuales fueron seleccionadas con base en estudios previos sobre etiquetado de alimentos y las preguntas disponibles en la ENSANUT 2018. Se incluyeron las siguientes variables grupo de edad (18 a 49, 50 a 64, 65 y más) [24], sexo (masculino, fe-masculino) [25], nivel educativo (ninguno o centro de alfabetización, educación básica, media superior, superior) [24], estado civil (sin pareja, con pareja) [26,27], área de residencia (urbana, rural), región geográfica (sierra, costa, Amazonía, insular), pobreza por necesidades básicas insatisfechas (no pobre, pobre) [28,29], etnia (no indígena, indígena) [30] y comprensión del semáforo nutricional (no, sí) [24]. En cuanto a la pobreza por necesidades básicas insatisfechas, en nuestro estudio un hogar se clasificó como pobre si presentaba alguna de las siguientes características del hogar: alta dependencia económica, características físicas inadecuadas, hacinamiento, sin acceso a servicios básicos y aquellos con niños que no asisten a la escuela [31,32].Análisis estadístico El tratamiento y análisis de los datos se realizó con el programa estadístico Stata 17 (Stata Corporation, College Station, TX, EE.UU.).…”
Section: Variables Independientesunclassified